Gen Zers’ Stances on The Religion Role in Human Salvation - Bernardus Ario Tejo Sugiarto; Dadang Kahmad; Yeni Huriani (Jaqfi: Jurnal Aqidah dan Filsafat Islam, 2022)
Each generation has its character because of the differences in era context. The Z Generation (Gen Zers) also has distinctive features that are different from the previous generation. Gen Zers is a generation that lives in the context of the world that is strongly influenced by scientific and digital technological advances in all fields, especially in communication and information fields. In Western countries, there are serious symptoms of a decline in the number of Gen Zers who are affiliated with a religion or who attended Church. They think that being affiliated with a religion or attending Church isn’t something very important. Yet, it doesn’t mean that they disregard the values of spirituality and morality. On the contrary, they are deeply concerned with universal spiritual and moral values. For them, spirituality and morality are “yes”, but religion is “no”. The study’s purpose is to investigate the role of religion according to Gen Zers’ opinions in Bandung. The study method is a quantitative method that makes use of an e-questionnaire as a data collection tool. All respondents are students who are studying at a certain private university in Bandung. The main finding is almost all respondents opine that affiliating with religion isn’t determining factor for human salvation even though they are affiliated with a religion. The conclusion is that there are at least five ambiguous stances of Gen Zers on the role of religion in human salvation. They are religious formalism, agnosticism, religious indifferentism, practical atheism, and religionism.